2005
DOI: 10.1073/pnas.0504922102
|View full text |Cite
|
Sign up to set email alerts
|

Mutually dependent secretion of proteins required for mycobacterial virulence

Abstract: The ESX-1 locus is a region critical for full virulence in Mycobacterium tuberculosis, which encodes two secreted proteins as well as other genes involved in their secretion. The mechanism of secretion of the two proteins, ESAT-6 and CFP-10, and their function remain unknown. Using proteomic methods to search for additional proteins secreted by the ESX-1 locus, we discovered that a protein encoded by a chromosomally unlinked gene, espA, is also secreted by strains that contain the ESX-1 locus but not by strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
412
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(421 citation statements)
references
References 27 publications
7
412
1
1
Order By: Relevance
“…This secretion defect was not accompanied by an increase in cellular levels of PE25 and PPE41. This phenomenon is often observed for ESX-1 and ESX-5 substrates and indicates that the stability of the substrates depends on the presence of the T7S systems in the bacterial cell (5,11,13,33). PPE41 was detected in two forms, a 25-kDa band, which represents full-length PPE41, and a smaller form of ∼19 kDa, which probably represents degraded PPE41 (20).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This secretion defect was not accompanied by an increase in cellular levels of PE25 and PPE41. This phenomenon is often observed for ESX-1 and ESX-5 substrates and indicates that the stability of the substrates depends on the presence of the T7S systems in the bacterial cell (5,11,13,33). PPE41 was detected in two forms, a 25-kDa band, which represents full-length PPE41, and a smaller form of ∼19 kDa, which probably represents degraded PPE41 (20).…”
Section: Resultsmentioning
confidence: 98%
“…The archetypical T7S system, ESX-1, is responsible for the secretion of several proteins, including the ESX-1-encoded T-cell antigens ESAT-6 (early secreted antigenic target of 6 kDa) and CFP-10 (culture filtrate protein of 10 kDa) (7,(11)(12)(13)(14)(15). ESX-1 and its substrates play an important, albeit not yet fully understood role in M. tuberculosis virulence.…”
mentioning
confidence: 99%
“…As a result, one of the central aims of this work was to thoroughly test the capacity of M-PFC to reveal undefined Mtb virulence mechanisms. Several studies (16,17,(20)(21)(22) have shown that proteins in and outside of the Mtb RD1 region are involved in the secretion of the immunogenic antigens, Esat-6 and Cfp-10. An important feature of this yet-undefined specialized secretion system is that these small effector proteins contain no signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are components of the ESX-1 secretion system, which is primarily associated with mycobacterial virulence (Fortune et al, 2005;MacGurn et al, 2005;Raghavan et al, 2008), although in M. smegmatis, the ESX-1 system is also involved in DNA conjugation (Coros et al, 2008;Flint et al, 2004). The basis for the downregulation of the RecA-NDp and ESX-1 genes is unknown, but we speculate that these genes are regulated by an alternative sigma factor that is at a competitive disadvantage in the presence of increased levels of SigA, or has reduced expression in TB294-pSigA.…”
Section: Discussionmentioning
confidence: 99%